2012
DOI: 10.1021/je200766t
|View full text |Cite
|
Sign up to set email alerts
|

Vapor–Liquid Equilibria of Glycerol, 1,3-Propanediol, Glycerol + Water, and Glycerol + 1,3-Propanediol

Abstract: Vapor−liquid equilibria of two compounds, glycerol (or 1,2,3-propanetriol) and 1,3-propanediol, and two mixtures, glycerol + water and glycerol + 1,3-propanediol, were determined using a static apparatus. The obtained pressure values range from 6 Pa to 45 kPa for the compounds and from (32 to 163) kPa for the mixtures. From the temperature dependence of the vapor pressures, the molar enthalpies of vaporization at the mean temperature of the experimental range were derived from the Clausius−Clapeyron equation. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
25
1
2

Year Published

2013
2013
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 22 publications
(30 citation statements)
references
References 31 publications
(71 reference statements)
2
25
1
2
Order By: Relevance
“…The calculated results are compared with the experimental and literature values and shown in Figure 8. As γ 13 ∞ is concerned, the results of the present correlation are in good agreement with the experimental values and are slightly larger than the literature values of Ikari and Ayabe (cited in Kojima et al 21 ) and the calculated values of Mokbel et al 23 Further, the literature values of Bestani and Shing 25 appears to be unusually great, whereas the correlations of Souza et al, 3 Pla-Franco et al, 4 and APV80 VLE-IG provide values that are unusually small. Because the infinite dilution state is closely related to the process of glycerol recovery, such large deviations in γ 13 ∞ would have significant impact on the design of the recovery unit.…”
Section: Journal Of Chemical and Engineering Datasupporting
confidence: 88%
“…The calculated results are compared with the experimental and literature values and shown in Figure 8. As γ 13 ∞ is concerned, the results of the present correlation are in good agreement with the experimental values and are slightly larger than the literature values of Ikari and Ayabe (cited in Kojima et al 21 ) and the calculated values of Mokbel et al 23 Further, the literature values of Bestani and Shing 25 appears to be unusually great, whereas the correlations of Souza et al, 3 Pla-Franco et al, 4 and APV80 VLE-IG provide values that are unusually small. Because the infinite dilution state is closely related to the process of glycerol recovery, such large deviations in γ 13 ∞ would have significant impact on the design of the recovery unit.…”
Section: Journal Of Chemical and Engineering Datasupporting
confidence: 88%
“…But it has turned out that new vapour pressures measured by static method recently [14] were slightly higher (see figure S1) in comparison to our published transpiration results [4]. In order to ascertain a vapour pressure dataset, in this work we have repeated transpiration experiments on 1,3-propanediol especially at temperatures above 333 K where the discrepancies were more apparent.…”
Section: Vapour Pressures Of 13-propanediolmentioning
confidence: 81%
“…A general good agreement was observed for the available in the literature absolute vapour pressures. In the meantime, an extended GC-correlation study of a,x-alkanediols was published by Chickos et al [13], as well as a very careful vapour pressure measurements were reported from the static method just recently [14]. We also overlooked in reference [4] vapour pressures measured by ebulliometry [15] and by the thermogravimetry [16].…”
Section: Vapour Pressures Of 13-propanediolmentioning
confidence: 98%
“…1is not informative enough. More detailed insight in the quality of vapor pressures measured with different methods [14,[16][17][18][19][20][21][22][23][24][25] can be obtained from the "arc representation" developed by Oonk et al [26][27][28].The main idea of this approach is to collect all available data in a possibly broad temperature range and to approximate vapor pressures at the beginning and the end of the temperature range with the linear equation.…”
Section: Evaluation Of Vapor Pressures Of Glycerolmentioning
confidence: 99%
“…- [19];  -Knudsen [20]; □ -TGA [22]; ○ -Knudsen [21]; △ -static method [25]; ▽ -TGA [23]; ▷ -ebulliometry [17]; ◁ -not available method [24];  -ebulliometry [16];…”
Section: 8strength Of Hydrogen Bonding In Glycerolmentioning
confidence: 99%